Expression of p53 in toluidine blue positive oral squamous cell carcinoma lesions and expression of Ki67 in vinegar positive oral squamous cell carcinoma lesions - Kanokporn Bhalang; Kittipong Danuthai (Frontiers Media S.A., 2023)
The aims of this study were to investigate the sensitivity and specificity of toluidine blue and/or vinegar in oral cancer screening and to examine the correlation between clinical screening using toluidine blue and vinegar and the expression of the tumor marker p53 and proliferation marker Ki67, respectively. The study consisted of 87 patients with suspected oral squamous cell carcinoma lesions. Toluidine blue and/or vinegar were applied to the lesions, followed by biopsies. The tissues were diagnosed histopathologically and underwent immunohistochemical process for p53 or Ki67. The results revealed that the sensitivity and specificity of oral cancer screening using toluidine blue were 93% and 46%, respectively; whereas the sensitivity and specificity using vinegar were 85% and 81%, respectively. A statistically significant correlation between the use of vinegar and the expression of Ki67 (p = 0.019) was observed. Although there was a difference in the expression of p53 between specimens that were positive and negative to toluidine blue, the correlation did not reach a significant level. Based on the results from this study, vinegar has a lower sensitivity than toluidine blue but a higher specificity for oral cancer screening. The results of the clinical screening using vinegar correlated with the expression of Ki67 at the cellular level.